Microbiological Evaluation of Incinerator Operations - Peterson, Mirdza L. (1969)
Incineration is currently a widely used method for the disposal of municipal solid waste in major American cities. The efficacy of several incinerator types to destroy bacteria associated with solid waste was evaluated, with emphasis on fecal and food sources. Samples of solid waste and its residue after incineration, taken from four incinerators of different design, were homogenized in phosphate buffer at pH 7.5. Samples of these homogenates were quantitatively examined for (i) total bacterial cell number, (ii) total coliforms, (iii) fecal coliforms, and (iv) heat-resistant spore-formers. Survival of coliforms in the residue after incineration was considered an indication of inadequate incinerator design or operation, or both. Of the four incinerators tested, only one produced residue devoid of fecal coliforms; three others produced residue containing fecal coliform populations of 5 to 2,400 per g. An inverse relationship was noted between the efficacy of incinerators in destroying fecal coliforms and the heat resistance (80 C) of total bacterial populations surviving in their respective residues. This could be due to the selection of heat-resistant cells during incineration.